PELAKSANAAN EVALUASI RANAH AFEKTIF MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 SUMATERA BARAT - Mursalin Mursalin (IAIN Batusangkar, 2016)
This study was purposed at indentifying the implementation of affective assessment in Islamic education of State High School 1 West Sumatera. This study was used qualitative case study approach by applying observation, interview, and documentation on collecting data. The data were analyzed by using qualitative analysis based on Miles and Huberman’s theory. The results obtained in this study indicate that the teachers had applied affective assessment very well. The teachers did not only focus on cognitive aspect but also on affective aspect. The steps of affective assessment were planning, implementing, analyzing and reporting the result of assessment.Keywords: Affective Assessment, Islamic Education, High School, West Sumatera